Alginate-based aerogels with double catalytic activity sites and high mechanical strength. (1st October 2020) - Hou, Yaheng; Zhong, Xin; Ding, Yangyang; Zhang, Shenghu; Shi, Fengwei; Hu, Jianglei
Graphical abstract: Highlights: Alginate-based aerogels with high mechanical strength and catalytic performance. Alginate-based aerogels catalyst with double catalytic activity centers. SiO2 and GO enhance the mechanical property of aerogel catalysts. GO plays as the second catalytic activity center. Abstract: Aerogel nanocomposites from biomass are one of the attractive emerging materials in the field of material chemistry and catalyst industry, but their lower catalytic efficiency and mechanical performance have limited their wide range applications. In this work, alginate-based aerogels with perfect catalytic performance and great mechanical strength were prepared through incorporating graphene oxide (GO) and SiO2 via a simple one-pot reaction. GO played as the second catalytic activity sites and endowed the aerogels the perfect catalytic performance (conversion of phenol reached 90.1 % in phenol hydroxylation reaction). Meanwhile, SiO2 and GO could improve the particle compressive strength of the aerogel to 36.0 kg/cm 2 . This alginate-based aerogel provides a novel and environmentally friendly catalyst for next generation catalytic industry.